An Accurate Skeleton Extraction Approach From 3D Point Clouds of Maize Plants - Wu, Sheng; Wen, Weiliang; Xiao, Boxiang; Guo, Xinyu; Du, Jianjun; Wang, Chuanyu; Wang, Yongjian (Frontiers in Plant Science, 2019)
Accurate and high-throughput determination of plant morphological traits is essential for phenotyping studies. Nowadays, there are many approaches to acquire high quality three-dimensional (3D) point clouds of plants. However, it is difficult to estimate phenotyping parameters accurately of the whole growth stages of maize plants using these 3D point clouds. In this paper, an accurate skeleton extraction approach was proposed to bridge the gap between 3D point cloud and phenotyping traits estimation of maize plants. The algorithm first uses point cloud clustering and color difference denoising to reduce the noise of the input point clouds. Next, the Laplacian contraction algorithm is applied to shrink the points. Then the key points representing the skeleton of the plant are selected through adaptive sampling, and neighboring points are connected to form a plant skeleton composed of semantic organs. Finally, deviation skeleton points to the input point cloud are calibrated by building a step forward local coordinate along the tangent direction of the original points. The proposed approach successfully generates accurately extracted skeleton from 3D point cloud and help to estimate phenotyping parameters with high precision of maize plants. Experimental verification of the skeleton extraction process, tested using three cultivars and different growth stages maizes, demonstrates that the extracted matches the input point cloud well. Compared with 3D digitizing data derived morphological parameters, the RMSE of leaf length, leaf inclination angle, leaf top length, leaf azimuthal angle, height of leaf position, and plant height, estimated using the extracted plant skeleton, are 2.645 cm, 2.737°, 2.357 cm, 4.432°, 1.753 cm, and 1.85 cm respectively, which could meet the needs of phenotyping analysis. The time required to process a single maize plant is below 100 seconds. The proposed approach may plays an important role in further maize research and applications, such as genotype-to-phenotype study, geometric reconstruction, functional structural maize modeling, and dynamic growth animation.